2017
DOI: 10.3329/bjms.v16i1.31137
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hospital Accreditation and Patient Satisfaction: A Survey in the Western Province of Iran

Abstract: Abstract:Background: In recent years accreditation programs have been developed to assess the quality of care and patient safety in hospitals. Quality is a multidimensional concept with patient satisfaction as one of the important facets. This study aimed to test any relationship between patient satisfaction and hospital accreditation. Material and Methods: A cross-sectional study of seven hospitals in Hamadan, Iran, was conducted in 2013. Patient satisfaction was analyzed through a self-made questionnaire and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
0
17
1
Order By: Relevance
“…Additional research is needed to obtain a better understanding of the patient satisfaction viewpoint expressed on social media regarding both accredited and non-accredited hospitals. According to the findings of a Lebanese study, tangible hospital characteristics such as physical facilities and equipment have an effect on patient satisfaction [ 43 ], a result that has been confirmed by other research [ 45 , 61 ]. Other patient perspectives or quality domains that contribute to patient satisfaction include emergency and inpatient care, triage length, and respect for patients [ 59 , 74 ].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Additional research is needed to obtain a better understanding of the patient satisfaction viewpoint expressed on social media regarding both accredited and non-accredited hospitals. According to the findings of a Lebanese study, tangible hospital characteristics such as physical facilities and equipment have an effect on patient satisfaction [ 43 ], a result that has been confirmed by other research [ 45 , 61 ]. Other patient perspectives or quality domains that contribute to patient satisfaction include emergency and inpatient care, triage length, and respect for patients [ 59 , 74 ].…”
Section: Discussionmentioning
confidence: 81%
“…Earlier research established that accreditation was not linked with patient satisfaction [ 40 , 41 ] and that there was no statistically significant difference in patient satisfaction or recommendation between accredited and non-accredited hospitals [ 42 ]. This finding was supported by a study conducted in Lebanon in which the majority of patients expressed dissatisfaction with the quality of services [ 43 ], a study conducted in the United States in which no significant difference in patient satisfaction was found between accredited hospitals and other organizations [ 44 ], and an Iranian study in which an inverse relationship between patient satisfaction and quality of care was discovered [ 45 ]. However, many other studies have shown a positive correlation between accreditation and patient satisfaction in several settings, including Southeast Asia [ 46 ] and the Middle East [ 47 , 48 ].…”
Section: Theoretical Backgroundmentioning
confidence: 79%
“…Another study conducted by Mosadeghrad et al (2017) showed that Iran's accreditation standards emphasized work structures and processes, and the number of outcome measures and its result were very limited (33). Mohebbifar (2017) also obtained a significant negative correlation between the scores of hospital accreditation and patients'outcomes (34). A study on 36,777 patients in 73 hospitals in Germany (2010) showed that accreditation did not lead to patients' satisfaction (35), which was found to be consistent with the distribution of components and evaluation in this study.…”
Section: Discussionmentioning
confidence: 98%
“…39 Mohebbifar and colleagues (2017) found a negative association between hospitals' accreditation scores and patient satisfaction in seven hospitals in Hamedan province, Iran. 44 The HAP has four components: governance, standard, method, and surveyor. 2 The inefficacy of the HAP is related to an ineffective hospital accreditation system (i.e., governance and leadership, accreditation standards, evaluation methods and accreditation surveyors) and inappropriate standards implementation in hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Pourreza and colleagues (2017) reported no association between implementing accreditation standards in the emergency and accident department and key performance indicators in eight hospitals 39 . Mohebbifar and colleagues (2017) found a negative association between hospitals’ accreditation scores and patient satisfaction in seven hospitals in Hamedan province, Iran 44 …”
Section: Introductionmentioning
confidence: 99%